Intra- and inter-specific density dependence of body condition, growth, and habitat temperature in chub mackerel (Scomber japonicus). (1st October 2021) - Kamimura, Yasuhiro; Taga, Makoto; Yukami, Ryuji; Watanabe, Chikako; Furuichi, Sho
Abstract: The density dependence of growth and body condition have important impacts on fish population dynamics and fisheries management. Although population density affects habitat selection, which in turn changes habitat temperature, how this affects growth and body condition remains unclear. Here, we investigated annual changes in body condition, habitat temperature, and cohort-specific growth of chub mackerel ( Scomber japonicus ) in the western North Pacific and examined quarterly changes in the density dependence of body condition. We hypothesized that chub mackerel body condition is affected both directly (e.g. through competition for food) and indirectly (through changes in habitat temperature) by the abundance of both conspecifics (i.e. chub mackerel) and heterospecifics (the Japanese sardine Sardinops melanostictus ). Indeed, chub mackerel body condition, habitat temperature, and growth all decreased with increasing conspecific and heterospecific abundance. Mean annual growth rates in chub mackerel were positively corelated with body condition. The final model showed that conspecific and/or heterospecific abundance had strong negative effects on chub mackerel body condition in all seasons, and influenced habitat temperature through habitat selection in some seasons. By contrast, temperature effects on body condition were weak. Therefore, direct effects likely have more impact than indirect effects on density-dependent body condition and growth.